2008
DOI: 10.1158/1078-0432.ccr-07-4418
|View full text |Cite
|
Sign up to set email alerts
|

In vivoOptical Coherence Tomography Imaging of Preinvasive Bronchial Lesions

Abstract: Purpose: Optical coherence tomography (OCT) is an optical imaging method that can visualize cellular and extracellular structures at and below tissue surface. The objective of the study was to determine if OCT could characterize preneoplastic changes in the bronchial epithelium identified by autofluorescence bronchoscopy. Experimental Design: A 1.5-mm fiberoptic probe was inserted via a bronchoscope into the airways of 138 volunteer heavy smokers participating in a chemoprevention trial and 10 patients with lu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
125
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 187 publications
(127 citation statements)
references
References 32 publications
1
125
0
1
Order By: Relevance
“…OCT can be used to conduct large-volume in vivo microscopy of tissue with resolutions comparable to low-power microscopy (18). OCT has been used to accurately detect and diagnose pathology in vivo for a number of years (17)(18)(19)(20)(21)(22)(23)(24) and has been used to assess the fine microarchitectural features in both normal and pathologic lung (25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42)(43).…”
mentioning
confidence: 99%
“…OCT can be used to conduct large-volume in vivo microscopy of tissue with resolutions comparable to low-power microscopy (18). OCT has been used to accurately detect and diagnose pathology in vivo for a number of years (17)(18)(19)(20)(21)(22)(23)(24) and has been used to assess the fine microarchitectural features in both normal and pathologic lung (25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42)(43).…”
mentioning
confidence: 99%
“…(27) In lung cancer, OCT has been used for differentiating normal mucosa from pre-neoplastic lesions. Three groups of authors (28)(29)(30) studied the tracheobronchial trees of patients suspected of having cancer and compared OCT images with images of biopsy of suspicious sites; the authors concluded that OCT, in addition to being well tolerated, was able to differentiate between normal tissue and tissue with neoplastic infiltration, suggesting that OCT can be an adjuvant technique in the early diagnosis of neoplastic lesions.…”
Section: Discussionmentioning
confidence: 99%
“…Optical coherence tomography has been used to assess the pulmonary airways and parenchyma in animal models [56][57][58][59][60][61] and in vivo human airway. [62][63][64][65][66][67][68] Optical coherence tomography imaging of the normal bronchial wall (Figure 4, A through E) reveals the fine, layered features of the airway, including the epithelium, basement membrane, lamina propria, salivary-type glands and ducts, vessels, and cartilage with surrounding perichondrium. In more distal airways, airway layering and attached lattice-like, signalvoid alveoli can be appreciated.…”
Section: Oct In Pulmonary Imagingmentioning
confidence: 99%
“…64,66,67 The ability of OCT to discern preinvasive cancers of the bronchial mucosa has been assessed. 67,68 Lam et al 68 used OCT to evaluate bronchial mucosal lesions identified by autofluorescence bronchoscopy in a group of high-risk smokers. A total of 281 OCT images were evaluated from 148 patients (145 normal/hyperplasia, 61 metaplasia, 39 mild dysplasia, 10 moderate dysplasia, 6 severe dysplasia, 7 carcinoma in situ, and 13 invasive carcinomas).…”
Section: Oct In Pulmonary Imagingmentioning
confidence: 99%